Peningkatan Minat dan Motivasi Belajar Siswa SMP Negeri 2 Gerung Dengan Menggunakan Model Jelajah Alam Melalui Pembelajaran Cooperative Learning - Anak Agung Ayu Diah Kusumadewi; Agus Ramdani; Akhmad Badrul Ula (Universitas Mataram, 2022)
Exploration of the Surrounding Nature (JAS) is a learning strategy that focuses on utilizing the physical and social environment to encourage students to detect things, symptoms, and problems, and come to conclusions about the concept of something they are learning. This study aims to use the model of exploring nature and cooperative learning to find out and analyze the interests and motivations of students at SMP Negeri 2 Gerung. This series of activities starts from the planning stage which includes the submission of devotion letters, then continues with observations and interviews with science teachers about student learning conditions. There were 21 seventh grade students at SMPN 2 Gerung as samples. At the implementation stage, activities were carried out to increase students' interest and motivation in learning by using the model of exploring nature through cooperative learning to students related to science learning, which was then followed by students filling out questionnaires, in this case by class VII. This final assessment or evaluation stage involves collecting and processing questionnaire data, which is then displayed in graphs or tables. Based on the results of the student learning interest questionnaire, in general, of the 15 aspects of the statements given, the highest percentage lies in statements one and eight, which is 81.0%. While the lowest percentage is in the 13th statement of 44.8% related to the lack of students in understanding the teacher's explanations that focus on the material. From the student learning motivation questionnaire, the lowest percentage is 48.8%. While the highest percentage of 82.1% on the statement indicator Completing the tasks in this learning makes me feel satisfied and happy with the results that I have achieved. By using the nature exploration learning model with the Cooperative Learning method, in general students can feel motivated and also interested in participating in science learning according to the results of the student learning interest questionnaire, the first statement is